Asymmetric Effects of Real Exchange Rate on Trade Balance in Cote d’Ivoire: Evidence from Nonlinear ARDL Approach - Keho, Yaya (Redfame, 2021)
This paper analyses the effects of real exchange rate on the trade balance in Cote d’Ivoire using times series from 1975 to 2017. Although many studies have investigated this issue, most of them assume that this relationship is symmetric. This paper relaxes this assumption employing the nonlinear autoregressive distributed lag (ARDL) model by Shin, Yu and Greenwood-Nimmo (2014). The results show that trade balance responds stronger to negative shocks in real exchange rate than to positive ones in the long-run, while the short-run response of trade balance is symmetric.
Applied Economics and Finance, Volume 8, No. 3
Keywords: trade balance; real exchange rate; nonlinear ARDL; Cote d’Ivoire; École Nationale Supérieure de Statistique et d'Economie Appliquée d'Abidjan (ENSEA); Social/Econ Science